Optimalisasi Penguatan Kompetensi Guru Bimbingan dan Konseling Melalui Pelatihan Pembuatan RPLBK Berbasis Four C’s - Silvia AR; Nur Wisma; Alrefi; Riski Novirson (Forum Kerjasama Pendidikan Tinggi, 2025)
The increasingly complex demands of the modern era require educational services, including guidance and counseling, to transform and align with the needs of 21st-century learners. School counselors play a strategic role in guiding students to develop their potential and plan their future careers effectively. However, a needs assessment conducted in Ogan Ilir Regency revealed that many school counselors still face challenges in designing Counseling Service Implementation Plans (RPLBK) based on 21st-century skills, known as the Four C’s: Critical Thinking, Creativity, Collaboration, and Communication. This community service activity aimed to enhance the professional competence of school counselors through a structured training program focused on developing RPLBK aligned with the Four C’s framework. The training was delivered using a blended learning model with an in-on-in approach, including theoretical sessions, face-to-face workshops, and follow-up mentoring for revision and evaluation. The evaluation results indicated a significant improvement in participants’ understanding and skills in designing more creative, collaborative, and contextually relevant RPLBKs. This initiative is expected to serve as a starting point in strengthening the professional capacity of school counselors to provide adaptive and relevant career guidance services in the digital era.